2020
DOI: 10.1080/02687038.2020.1752907
|View full text |Cite
|
Sign up to set email alerts
|

Aphasia and Spirituality: the feasibility of assessment and intervention using WELLHEAD and SHALOM

Abstract: Background: Spiritual aspects of aphasia rehabilitation are poorly understood, though identified within adjustment. Existing spiritual health assessments have not been used with people with aphasia, and no structured program to facilitate intervention has been documented, despite acknowledgments that spirituality is important in health and wellbeing and distinct from quality of life and mental health.Aims: Mixed methods were used to investigate the accessibility and acceptability of a spiritual health assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Twenty research reports described qualitative research, eight of which used a phenomenological approach (Brown et al, 2010(Brown et al, , 2011a(Brown et al, , 2011bGrohn et al, 2012Grohn et al, , 2014Lanyon et al, 2018;Panda et al, 2021;Pringle et al, 2010). Two articles reported on mixed-methods research (Bronken et al, 2012;Mumby & Roddam, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty research reports described qualitative research, eight of which used a phenomenological approach (Brown et al, 2010(Brown et al, , 2011a(Brown et al, , 2011bGrohn et al, 2012Grohn et al, , 2014Lanyon et al, 2018;Panda et al, 2021;Pringle et al, 2010). Two articles reported on mixed-methods research (Bronken et al, 2012;Mumby & Roddam, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 31 final articles reviewed, four articles were found using the search term "resilience" (Dietz et al, 2020;Hunting Pompon et al, 2018;Moss et al, 2021;Panda et al, 2021). Thirteen articles were found using "adaptation" (Brown et al, 2010(Brown et al, , 2011a(Brown et al, , 2011bDonnellan et al, 2012;Grohn et al, 2012;Hinckley, 2015;Laures-Gore et al, 2020;Moss et al, 2021;Northcott et al, 2021;Pringle et al, 2010;Wray et al, 2019Wray et al, , 2020Wray & Clarke, 2017), 14 articles were found using "adjustment" (Bronken et al, 2012;Grohn et al, 2012Grohn et al, , 2014Laures-Gore et al, 2020;Moss et al, 2021;Mumby & Roddam, 2021;Mumby & Whitworth, 2013;Musser et al, 2015;Nätterlund, 2010;Sherratt & Simmons-Mackie, 2016;Tregea & Brown, 2013;Wray et al, 2019Wray et al, , 2020Wray & Clarke, 2017), and 11 articles were found using "coping" (Armstrong et al, 2015;Bragstad et al, 2020;Dietz et al, 2020;DuBay et al, 2011;Harmon, 2020;Hjelle et al, 2019;…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A feasibility study of the WELLHEAD spirituality toolkit using a case series of 10 people with aphasia was conducted in a health service outpatient setting in accordance with health research authority ethical approval (Study reference: IRAS id 216 799 https://www.hra.nhs.uk/planning-and-im proving-research/application-summaries/research-summaries/aphasia-and-spirituality-toolkit-pilot -study-version-1/). The overarching findings are being reported in detail elsewhere, (Mumby and Roddam 2019; see also Mumby and Roddam 2018) with the focus here upon in-depth dialogue with a participant with TBI. Prior to the study, a steering group of people with aphasia collaborated with the researcher to select the spiritual health assessment, Spiritual Health and Life Orientation Measure (SHALOM (Fisher 2010)), from the existing published resources.…”
Section: A Single Case Narrative From a Case Seriesmentioning
confidence: 87%
“…The measurements gathered using WELLHEAD supplemented the qualitative analysis, but they did not stand alone, being part of a prototype. The measures will form part of a larger data set concerning aphasia (including findings from the feasibility study being reported by Mumby and Roddam (2019)). Preliminary comparisons of SHALOM and WELLHEAD indicated that they were mutually compatible (see Section 3.4), and that the WELLHEAD interview provided rich data about personal perceptions and the processes involved in spirituality; not accessible from measurements alone.…”
Section: Discussionmentioning
confidence: 99%